PSYCHOLOGICAL PROFILES OF STUDENTS MAJORING IN HUMANITIES: CLUSTER ANALYSIS - Mosinyan-Meier, Violeta; Avanesyn, Hrant (Modern Psychology, 2025)
In this study, we define the psychological profiles (PP) of students in the humanities (SHF) of Armenia and Germany. The objective of this work is to empirically identify stable clusters that differ in the degree of anxiety, self-esteem and motivation of students. The hypothesis of the study is that in the Armenian and German samples of SHF there are clusters that differ in the stability of the emotional background, expressed anxiety and motivational types. The study involved 600 SHF (300 from Armenia, 300 from Germany); the average age in Armenia was 23 years, in Germany - 32 years. The STAI, Budassi S.A. and the academic motivation technique of Gordeeva L.G. and Osin E.N. were used. The data were processed using the methods of correlation, variance and cluster analysis. The results of the study showed that SHF of Armenia are dominated by a high level of anxiety, while SHF of Germany are more characterized by extrinsic motivation. Cluster analysis identified four stable PPs: emotionally stable, flexibly motivated, anxious-dependent, and uncertain-contradictory. The findings confirm the relationship between anxiety, self-esteem, and motivation, as well as the importance of intrinsic motivation for successful adaptation of the SHF.
Keywords: student; humanities; cluster analysis; psychological profiles; anxiety; self-esteem; academic motivation; self-regulation; emotional stability; Armenia; Germany